Intraocular Pressure Changes Two-Six Hours, One Day, and One Week after Phacoemulsification Cataract Surgery and Implantation of Intraocular Lens - Ali Sharifi; Vares Tahmooresi; Mohammad Sharifi; Naser Nasiri; Hamid Sharifi (Journal of Kerman University of Medical Sciences, 2022)
Background: This study was conducted to evaluate the status of eye and intraocular pressure (IOP), two-six hours, one day, and one week after cataract surgery and implantation of the intraocular lens.Methods: In a longitudinal study, 159 patients with senile cataracts were evaluated. Phacoemulsification surgery and intraocular lens (IOL) implantation in the capsular bag was done. The examinations including visual acuity measurement, slit-lamp examination, and measurement of IOP were done preoperatively, and three times after the surgery.Results: The mean±standard deviation (range) age of the patients was 65.8 ± 10.5 (40-90) years. Preoperatively the IOP was 12.8 ± 3.5 mmHg, it increased to 20.8 ± 10.7, 2-6 hours after surgery (P < 0.0001), and then reached 13.7 ± 4.4 mmHg on the first postoperative day (P < 0.0001), then it decreased to 12.4 ± 2.9 mmHg one week after the surgery (P=0.02). The IOP was 28.6 ± 12.2 mmHg in eyes with epithelial edema which was significantly higher than those with stromal edema (17.3 ± 7.5 mmHg), and those without edema (16.5 ± 7.1 mmHg) 2-6 hours after surgery.Conclusion: Since the IOP spike can damage the structure and function of the eye and cause pain, discomfort, and corneal edema that in turn prolongs recovery of vision, especially in those previously damaged, early postoperative examination on the same day after cataract surgery is strongly advised. IOP spikes can be managed safely by aqueous paracentesis without oral, parenteral, or topical drugs. Elevated IOP is more prevalent in eyes with postoperative epithelial corneal edema and in individuals whose cornea is totally edematous.